Spatial and seasonal distributions of Callinectes danae (Decapoda, Portunidae) in Ubatuba Bay, São Paulo, Brazil - Chacur, M. M.; Negreiros-Fransozo, M. L. (Crustacean Soc, 2001)
The spatial and seasonal distributions of Callinectes danae Smith, 1869, in Ubatuba Bay, São Paulo, Brazil, were investigated as a part of a broad study on the general biology of portunids along the northern coast of São Paulo State, Brazil. Swimming crabs were collected during one year, from September 1995 to August 1996, along eight transects determined according to local physiographic features. Three replicate trawls were performed monthly at each transect. Depth. salinity, dissolved oxygen, temperature, organic matter content, and texture of the sediment were measured. Callinectes danae individuals were concentrated in shallow water close to the discharge of estuaries where the bottom is composed of fine and very fine sand. The species was more abundant in the warmer months. During the study period, C. danae exhibited continuous reproduction with a peak of reproductive intensity in June. Within this area, some sites are particularly favorable for C. danae establishment due to a combination of factors and prevailing local conditions.